PERKEMBANGAN PSIKOSOSIAL PADA MASA KANAK-KANAK AWAL - Pasaribu, Safrina Putri (AL-QALAM: JURNAL KEPENDIDIKAN, 2023)
Psychosocial development in early childhood is a critical phase in the formation of a holistic individual. This research digs deeper into the main aspects of child development during this period, with a particular focus on physical, cognitive development, self-concept, and gender perspectives as influenced by natural and nurturing factors. First, children's physical development during this period includes body growth, motor coordination, and mastery of fine motor skills. This research involves direct observation of physical changes and their impact on children's daily activities and social interactions. Second, cognitive development is the main focus by considering progress in understanding, language, and problem-solving abilities. This research investigates the role of gender perspectives in children's psychosocial development in early childhood. The nature and nurture approach is applied to understand the extent to which biological and nurturing factors contribute to children's understanding of gender, activity preferences and social interactions. By bringing together multiple dimensions of development in early childhood, this research provides holistic insight into how physical, cognitive development, self-concept, and gender perspectives are interrelated and influence each other. The practical implications of this research can help parents, educators, and policy makers in designing educational and parenting approaches that better support children's psychosocial development.